To the question of the definition of television documentary drama - Stezhko, Natalia G. (Journal of the Belarusian State University. Journalism, 2019)
The article explores the definition of television documentary drama. The genre appeared in the middle of the 20th century and immediately attracted the attention of film theorists. It is shown that docudrama originated at the junction of feature films and documentary films at the time when directors raised important social and historical issues that occurred in the state. It is suggested that the authors resorted to film staging due to lack of authentic photo- and film material and that strengthened the spectacular side of the audiovisual work. The article analyses the dual nature of docudrama that led to a great deal of disagreement among researchers about the concept of docudrama and its position in a single system of screen arts.